Misadventures and traps in stamp duty dodging in Singapore - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2024)
As stamp duty rates in Singapore have increased over time, so too have the number of stamp duty avoidance schemes, ranging from simple and straightforward to complex and elaborate. Even when these schemes technically succeed, any potential loopholes are quickly dealt with legislatively. But stamp duty avoidance attempts can also backfire with heavy resulting costs. Changes such as the stamp duty avoidance surcharge discourage aggressive planning. The most severe consequences occur when property buyers go beyond mere avoidance and enter the more dangerous territory like evasion. This article cautions against a range of missteps, each more serious than the last.